CROSS-LINGUISTIC INFLUENCE IN MALAYSIAN ESL LEARNERS WRITING: A CASE STUDY - Tati, Johan Severinus; Gedion, Annie; Yong, Helen (PEOPLE: International Journal of Social Sciences, 2015)
Studies on cross-linguistic influence have shed some lights on the general view of the processes involved when learning a second language which is different from the first language. This study aims to identify and describe aspects of cross-linguistic influence in the writings of Malaysian ESL. The subjects in this study were five students from the Kadazandusun ethnic who mostly speak their mother tongue and Malay language in their daily communication. They learned English as a second language from pre-school until form five at secondary school level. They have attended fully-funded government schools that use Malay language as a medium of teaching and learning. Thus, the students’ knowledge of and contact with English was mostly restricted to formal instruction at school. Data were collected from given written tasks. Besides that, a set of questionnaire were administered to elicit information on their language dominance and linguistic knowledge. The focus of data analysis was twofold; syntactic level (word order, subject use and present continuous tense) and lexical level (misspelling, borrowing and coinages). The findings of this study to suggest that forms and the meaning in the second language are expressed and formed by the learners’ language knowledge and use of the second language as well as by the influence of the first language.Studies on cross-linguistic influence have shed some lights on the general view of the processes involved when learning a second language which is different from the first language. This study aims to identify and describe aspects of cross-linguistic influence in the writings of Malaysian ESL. The subjects in this study were five students from the Kadazandusun ethnic who mostly speak their mother tongue and Malay language in their daily communication. They learned English as a second language from pre-school until form five at secondary school level. They have attended fully-funded government schools that use Malay language as a medium of teaching and learning. Thus, the students’ knowledge of and contact with English was mostly restricted to formal instruction at school. Data were collected from given written tasks. Besides that, a set of questionnaire were administered to elicit information on their language dominance and linguistic knowledge. The focus of data analysis was twofold; syntactic level (word order, subject use and present continuous tense) and lexical level (misspelling, borrowing and coinages). The findings of this study to suggest that forms and the meaning in the second language are expressed and formed by the learners’ language knowledge and use of the second language as well as by the influence of the first language.